Table of Content - -, (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. National initiative for human development an innovative strategy to rehabilitate and develop human capital in MoroccoFatima Ghmimed, Jaouad El Bazoui, Abdelouahed Bouberria2. The impact of the Companions on managing Hajj seasons and services in the first century of the Hijri eraShadia Abdul rahman Albalawi3. The relationship between parental upbringing and divorce in Saudi Society Utilizing Case Study Approach: A case study in Jeddah province for a sample of divorced men and womenDr. Yahya Turki Al-Khazraj, Mohammed Ahmed Alghamdi4. The Geographical Spread of The Corona Virus and The Economic Implications in Districts of Makka CityMs. Jalila Ali Hamad Jabri, Dr. Sami Salah Ghamry5. Temporal and spatial analysis of air temperature change trends (thermal anomalies)  in the Kingdom of Saudi Arabia during the period 1985-2016 ADReem Mohammed Alshehri6. Challenges of investing in heritage in the development plan in Morocco: The case of the Taza region – MoroccoYounes El Azzouzi
Keywords: Journal of Human and Social Sciences